SNaPshot Assay for the Detection of the Most Common CFTR Mutations in Infertile Men - Noveski, Predrag (PLoS One, 2014)
Congenital bilateral absence of vas deferens (CBAVD) is the most common CFTR-related disorder (CFTR-RD) that explains about 1–2% of the male infertility cases. Controversial data have been published regarding the involvement of CFTR mutations in infertile men with non-obstructive azoospermia and oligozoospermia. Here, we describe single base extension (SNaPshot) assay for detection of 11 common CFTR mutations: F508del, G542X, N1303K, 621+1G->T, G551D, R553X, R1162X, W1282X, R117H, 2184insA and 1717-1G->A and IVS8polyT variants. The assay was validated on 50 previously genotyped samples and was used to screen a total of 369 infertile men with different impairment of spermatogenesis and 136 fertile controls. Our results show that double heterozygosity of cystic fibrosis (CF) and CFTR-related disorder (CFTR-RD) mutations are found in a high percentage (22.7%) of infertile men with obstructive azoospermia, but not in other studied groups of infertile men. The SNaPshot assay described here is an inexpensive, fast and robust method for primary screening of the most common CFTR mutations both in patients with classical CF and CFTR-RD. It can contribute to better understanding of the role of CFTR mutations in impaired spermatogenesis, ultimately leading to improved management of infertile men.